The Combination of Immunomagnetic Bead-Based Cell Isolation and Optically Induced Dielectrophoresis (ODEP)-Based Microfluidic Device for the Negative Selection-Based Isolation of Circulating Tumor Cells (CTCs) - Chu, Po-Yu; Hsieh, Chia-Hsun; Wu, Min-Hsien (Frontiers in Bioengineering and Biotechnology, 2020)
Negative selection-based circulating tumor cell (CTC) isolation is able to harvest viable, label-free, and clinically meaningful CTCs from the cancer patients’ blood. Nevertheless, its main shortcoming is its inability to isolate high-purity CTCs, restricting subsequent CTC-related analysis. To address this issue, this study proposed a two-step optically-induced dielectrophoresis (ODEP) cell manipulation to process the cell sample harvested by negative selection-/immunomagnetic microbeads-based CTC isolation. The working mechanism is that the ODEP force acting on the cells with and without magnetic microbeads binding is different. Accordingly, the use of ODEP cell manipulation in a microfluidic system was designed to first separate and then isolate the cancer cells from other magnetic microbead-bound cells. Immunofluorescent microscopic observation and ODEP cell manipulation were then performed to refine the purity of the cancer cells. In this study, the optimum operating conditions for effective cell isolation were determined experimentally. The results revealed that the presented method was able to further refine the purity of cancer cell in the sample obtained after negative selection-based CTC isolation with high cell purity (81.6 86.1%). Overall, this study proposed the combination of immunomagnetic bead-based cell isolation and ODEP cell manipulation for the negative selection-based isolation of CTCs.